A meta-analysis of phosphatase activity in agricultural settings in response to phosphorus deficiency. (February 2022) - Janes-Bassett, Victoria; Blackwell, Martin S.A.; Blair, Gordon; Davies, Jess; Haygarth, Philip M.; Mezeli, Malika M.; Stewart, Gavin
Abstract: Phosphorus (P) is a key limiting factor in crop growth and essential for agriculture. As plant uptake of P is inefficient, it is commonly applied to maintain crop yields leading to a range of negative environmental issues when applied in excess. Additionally, P in mineral fertilisers is derived from mined rock phosphate, which is a finite resource that needs to be sustainably managed in order to maintain food security in the long-term. Phosphatase activity is one of several mechanistic responses to P deficiency in the plant-soil system, enabling the mineralization of organic P to increase P availability for both plants and soil organisms. In this study we address the need to further understanding of the role of phosphatase enzyme activity in P acquisition in agricultural settings, using a systematic review of the literature and subsequent meta-analysis. We find that monoesterase activity is inhibited by availability of inorganic P (−23%, −39.8 to −2.2%) yet is enhanced by the availability of organic P (+74%, 8.4–232.1%). This indicates that phosphatase enzyme activity is important in P deficient agricultural systems, yet that the availability of organic P is more important in determining phosphatase activity than the level of P deficiency. We also investigated the role of other factors such as nitrogen addition, pH of growth substrate and changes in plant composition and physiology but, none of these factors explained significant variance in the data. We highlight need for consistent recording and reporting of additional variables in association with phosphatase enzyme assay data, which is required to enable quantification of the potential utilisation of organic P resources in agriculture, and the contribution of phosphatase activity to P acquisition in both agricultural and semi-natural ecosystems. Graphical abstract: Image 1 Highlights: Phosphatase activity is one of many plant-soil system responses to P deficiency. Their importance in agricultural settings is not well understood. Meta-analysis compares activity in P deficient and sufficient conditions. Phosphatase is suppressed by availability of inorganic P and enhanced by organic P. Availability of organic P is more important in determining phosphatase activity.